Results of treatment with alemtuzumab in a Spanish cohort of patients with multiple sclerosis in the real world: The RealMS study - Eichau, Sara; López Ruiz, Rocío; Ruíz de Arcos, María; Ruiz-Peña, Juan Luis; Navarro, Guillermo; Calleja, Miguel Ángel; Moreno-Amador, José Luis; Dotor García-Soto, Julio (Frontiers in Neurology, 2023)
Background Alemtuzumab (ALZ) is a humanized monoclonal antibody approved for the treatment of patients with highly active relapsing-remitting multiple sclerosis (RRMS) administered in two annual courses. The objective of this study was to describe the effectiveness and safety data of ALZ and to report the health resource utilization in patients receiving this treatment. Methods In this retrospective, non-interventional study, information was retrieved from patients' medical charts at one center in Spain. Included patients were ≥18 years old, and ALZ treatment was initiated between 1 March 2015 and 31 March 2019, according to routine clinical practice and local labeling. Results Of 123 patients, 78% were women. The mean (standard deviation, SD) age of patients at diagnosis was 40.3 (9.1) years, and the mean time since diagnosis was 13.8 (7.3) years. Patients were previously treated with a median (interquartile range; IQR) number of two (2.0–3.0) disease-modifying treatments (DMTs). Patients were treated with ALZ for a mean (SD) of 29.7 (13.8) months. ALZ reduced the annualized relapse rate (ARR) (1.5 before vs. 0.05 after; p < 0.001) and improved the median EDSS (4.63 before vs. 4.00 after; p < 0.001). Most (90.2%) patients were relapse-free while receiving ALZ. The mean number of gadolinium-enhancing [Gd+] T1 lesions was reduced (1.7 before vs. 0.1 after; p < 0.001), and the mean number of T2 hyperintense lesions was maintained (35.7 before vs. 35.4 after; p = 0.392). A total of 27 (21.9%) patients reported 29 autoimmune diseases: hyperthyroidism (12), hypothyroidism (11), idiopathic thrombocytopenic purpura (ITP) (3), alopecia areata (1), chronic urticaria (1), and vitiligo (1). The mean number of health resources (outpatient visits, emergency room visits, hospital admissions, and tests performed in the hospital) used while patients were treated with ALZ progressively decreased from year 1 to year 4, except for a slight increase at year 2 of outpatient visits. Conclusion The ReaLMS study provides real-world evidence that ALZ can promote clinical and magnetic resonance imaging disease remission, as well as disability improvement in patients with MS, despite several prior DMT failures. The ALZ safety profile was consistent with data available from clinical trials and other real-world studies. Healthcare resource use was reduced throughout the treatment period.